La foi peut-elle soulever les montagnes ? - Jean-Pierre Van Staëvel (Revue des Mondes Musulmans et de la Méditerranée)
Through a presentation of the historiography of the beginnings of Almohad revolution in the mountains of southern Morocco, this paper raises methodological reservations about the application of the gellnerian segmentarist model to the the sociopolitical morphology of the Almohad tribes, in order to explain the strength of the initial mobilization of the movement. Based on a reassessment of some textual data insufficiently exploited until now, it is suggested that the eminent status of Ibn Tûmart, the founder of the movement, regardless of its role as a man of religion, has been shaped and nourished by the position of power which was occupied by his family in his original tribe, and more widely in the major tribal groups that ruled then the mountains of the High and Anti- Atlas. The article finally lead to a questioning of the existence in some mountain societies and away from production centers of the official written policy, of tribal structures and chiefdoms that could carry or accompany movements of religious reform, often seen reductively by historiography as the product of the sole initiative of a providential man .